The Analysis Study of Effects of Glucagon-Like Peptide-1 Receptor to Reduce Adverse Cardiovascular Events in Patients with Type 2 Diabetes Mellitus: A Comprehensive Systematic Review - Firmansyah, Radian Tommy; Amalia, Lydia Nur (International Medical Journal Corp. Ltd, 2024)
Background: The aim of this study to show about effects of glucagon-like peptide-1 receptor to reduce adverse cardiovascular events in patients with type 2 diabetes mellitus. Methods: By the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. Result: Eight publications were found to be directly related to our ongoing systematic examination after a rigorous three-level screening approach. Subsequently, a comprehensive analysis of the complete text was conducted, and additional scrutiny was given to these articles. Conclusion: GLP‐1 receptor agonists represent a relatively new class of drugs used for the treatment of T2DM. They are not only able to improve hyperglycaemia of diabetic patients but also directly influence in addition other significant risk factors for CVD such as high blood pressure, dyslipidaemia or obesity. These properties explain at least in part the positive results of the CV outcome studies for liraglutide, semaglutide, dulaglutide and albiglutide, all of which showed not only CV safety but also an improvement in CV prognosis.